2011
DOI: 10.4161/cc.10.11.15676
|View full text |Cite
|
Sign up to set email alerts
|

TRIP6 and LPP, but not Zyxin, are present at a subset of telomeres in human cells

Abstract: T he protection of chromosome ends requires the inhibition of DNA damage responses at telomeres. This inhibition is exerted in great part by the shelterin complex, known to prevent inappropriate ATM and ATR activation. The molecular mechanisms by which shelterin protects telomeres are incompletely understood. Recently, we have implicated for the first time a class of molecules, LIM domain proteins, in telomere protection. This protection occurred through interaction with shelterin, possibly through POT1, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Telomeres are nucleoprotein structures that protect chromosome ends, which are particularly vulnerable to progressive shortening during each round of DNA replication (telomere erosion) (Artandi and DePinho, 2010). Recently, Sheppard and colleagues uncovered an unanticipated role of TRIP6 in telomere protection (Sheppard and Loayza, 2010; Sheppard et al, 2011). At the very distal end of the telomere, a 300 bp single‐stranded portion (T‐loop) is present that prevents telomere ends from being recognized as break points by the DNA repair machinery (Karlseder, 2003).…”
Section: The Roles Of Trip6 In Tumorigenesis and Cancer Progressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Telomeres are nucleoprotein structures that protect chromosome ends, which are particularly vulnerable to progressive shortening during each round of DNA replication (telomere erosion) (Artandi and DePinho, 2010). Recently, Sheppard and colleagues uncovered an unanticipated role of TRIP6 in telomere protection (Sheppard and Loayza, 2010; Sheppard et al, 2011). At the very distal end of the telomere, a 300 bp single‐stranded portion (T‐loop) is present that prevents telomere ends from being recognized as break points by the DNA repair machinery (Karlseder, 2003).…”
Section: The Roles Of Trip6 In Tumorigenesis and Cancer Progressionmentioning
confidence: 99%
“…The T‐loop is held together by several proteins: most notably TRF1 and TRF2 respectively, POT1 and TIN2, collectively referred to as the shelterin complex (Donate and Blasco, 2011). TRIP6 and LPP (but not zyxin) directly interact with POT1, TRF1, TRF2 and TIN2 in human cells, arguing for an association of TRIP6 with the whole shelterin complex (Sheppard and Loayza, 2010; Sheppard et al, 2011). TRIP6 and LPP depletion leads to telomere dysfunction‐induced foci and DNA damage responses, which are typical signs for telomere erosion (Sheppard and Loayza, 2010; Sheppard et al, 2011).…”
Section: The Roles Of Trip6 In Tumorigenesis and Cancer Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the nucleus, TRIP6 has transcriptional cofactor activity and regulates the transcriptional responses of these pathways (Kassel et al., ; Diefenbacher et al., , ; Willier et al., ). Moreover, intranuclear TRIP6, but not Zyxin, associates with proteins ensuring telomere protection and hence may play a role in genome stability (Sheppard and Loayza, ; Sheppard et al., ). Accordingly, TRIP6 is engaged in key cellular processes such as cell migration, invasion, proliferation, differentiation and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has previously shown that members of a distinctive class of molecules called LIM proteins are implicated in telomere protection by repressing DDR at telomeres (Sheppard and Loayza, 2010; Sheppard et al, 2011). Specifically, LIM proteins TRIP6 and LPP belong to the Zyxin family (Kadrmas and Beckerle, 2004) and interact with the shelterin complex to prevent DDR activation at telomeres.…”
Section: Introductionmentioning
confidence: 99%